Rendimiento del tomate lycopersicum esculentum mill utilizando acolchado plástico fertigación y bajo invernadero - Iñaguazo Macas, Darwin José (2008)
The present investigation on the Yield of the tomato (Lycopersicum esculentum Mill) using padded plastic, fertigación and low hothouse, he/she was carried out in the canton Chilla, county of El Oro; The outlined objectives were: 1) to evaluate the Yield of the low tomato the effects of the padded one, 2) to Check four nutritious solutions in the different phases of development of the cultivation, and 3) economic Analysis of the yields, with fertilization of fertile (N+P+K) watering, but humitron (organic matter), with a dose of T1: 125 g, T2: 250 g, T3: 575 g, T4: 875 g, To: 0,00; You registers plant height after the transplant to the 30 and 45 days, days to the floración, palgas incidence and illnesses, days to the fructification to the crop, weight of fruits, yield for hectare, The averages of treatments were compared by means of Test. of Duncan with a level of significance of 99%. Hybrid airton, responded to the fertilization and padded of the floor, In this context we have that the best result was the dose of T4: 875 g/p, with more average with 234 fruits for plant, it corresponded to at the high level of fertilization, this is 875 g, then in falling order it follows the low level of 125 g, with 219 fruits for parcel; the level of 575 with 217 fruit and fourth place the level 250 with 212 fruits; The biggest yield with the high level of fertility with 875 g/p with a crop of 55.5 pounds